Direct growth of FeVO4 nanosheet arrays on stainless steel foil as high-performance binder-free Li ion battery anode - Lim, Tuti Mariana (2013)
Amorphous FeVO4 nanosheet arrays have been grown directly from a flexible stainless steel (SS) substrate by a facile template-free and catalyst-free chemical vapour deposition (CVD) method. These FeVO4 nanosheets showed superior Li storage properties, especially at high current densities.